To the questions about the social purpose of state - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
It  is  consider  various  scientific  approaches  to the  definition  and  nature  of  the  social state,  its  social mission. It is explain basic mechanism of the social state